Ceramic fiber reinforced Ti3SiC2 / SiC composite material and preparation method thereof

By introducing the Ti3SiC2 structure into the SiC composite material in situ and reinforcing it through ceramic fibers, the problem of insufficient uniformity and bonding in the SiC composite material in the prior art is solved, thereby improving the performance of the composite material and simplifying the preparation process.

CN119528594APending Publication Date: 2025-02-28QIANWAN INST OF CNITECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411653772.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when Ti3SiC2 is introduced into the SiC composite matrix, it is easy to lead to a decrease in uniformity and weak bonding with the matrix, affecting the performance of the composite material.

Method used

By reinforcing the Ti3SiC2/SiC composite composed of a ceramic fiber reinforcement and a ceramic matrix, the Ti3SiC2 structure is introduced into the SiC composite in situ by pressurized sintering or pioneer impregnation and cracking process, and the performance of the composite is improved through ceramic fiber reinforcement.

Benefits of technology

The performance of ceramic fiber-reinforced Ti3SiC2/SiC composites has been improved in the electrical conductivity, electromagnetic absorption, and anti-oxidation properties, while simplifying the preparation process and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528594A_ABST
    Figure CN119528594A_ABST
Patent Text Reader

Abstract

The invention relates to a ceramic fiber reinforced Ti3SiC2 / SiC composite material and a preparation method thereof, and belongs to the technical field of ceramic materials. The invention discloses a ceramic fiber reinforced Ti3SiC2 / SiC composite material. The ceramic fiber reinforced Ti3SiC2 / SiC composite material is composed of a ceramic fiber reinforcement and a ceramic matrix, the ceramic fiber reinforcement is a short ceramic fiber and / or continuous ceramic fiber preform, and the ceramic matrix contains Ti3SiC2 and SiC; the ceramic fiber reinforced Ti3SiC2 / SiC composite material is prepared from short ceramic fibers, a mixture composed of a polycarbosilane precursor, a titanium source and an auxiliary agent through pressure sintering, or the ceramic fiber reinforced Ti3SiC2 / SiC composite material is prepared from a continuous ceramic fiber preform and slurry containing the polycarbosilane precursor, the titanium source, the auxiliary agent and a solvent through a precursor impregnation cracking technology. The Ti3SiC2 structure is introduced into the SiC composite material in situ, so that the conductivity, electromagnetic absorption, oxidation resistance and other properties of the composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials and relates to a ceramic fiber reinforced Ti3SiC2 / SiC composite material and a preparation method thereof. Background Art

[0002] Ceramic fiber reinforced SiC composites have the advantages of good thermal stability, strong resistance to thermal shock, corrosion resistance, radiation resistance, etc., and exhibit "pseudo-plastic" fracture behavior under external force. They are widely used in heat-resistant parts of aerospace engines, thermal protection material systems of reusable carriers, and hypersonic transport propulsion systems. In addition, continuous ceramic fiber reinforced SiC composites have broad application potential in the fields of nuclear energy, high-speed brakes, hot end parts of gas turbines, high-temperature gas filtration and heat exchangers.

[0003] Ti3SiC2 is a widely studied MAX phase material with good thermal shock resistance, oxidation resistance, radiation resistance, electrical conductivity, lubricity and mechanical properties. Some researchers have introduced Ti3SiC2 into the SiC composite matrix to enhance the performance of ceramic fiber reinforced SiC composites. For example, Drexel University (J.Am.Ceram.Soc., 2011, 94(6):1737–1743) prepared SiC fiber-reinforced Ti3SiC2 matrix composites by hot pressing Ti3SiC2 powder, TiC powder and SiC fiber at 1500°C; Shanghai Institute of Ceramics, Chinese Academy of Sciences (Ceram.Int., 2016, 42(2):3019–3027) dispersed Ti3SiC2 phase into the matrix and prepared C f / Ti3SiC2-SiC composite material, forming a MAX matrix within the carbon fiber bundle.

[0004] It can be seen that in the current preparation methods of introducing Ti3SiC2 into the SiC composite matrix to enhance the performance of the composite material, the Ti3SiC2 phase is mostly directly filled into the composite matrix, which easily leads to reduced uniformity and weak bonding with the matrix. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and propose a ceramic fiber reinforced Ti3SiC2 / SiC composite material consisting of a ceramic fiber reinforcement and a ceramic matrix, introduce the Ti3SiC2 structure into the SiC composite material in situ, and add ceramic fiber reinforcement to effectively improve the performance of the composite material.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A ceramic fiber reinforced Ti3SiC2 / SiC composite material, which consists of a ceramic fiber reinforcement and a ceramic matrix; the ceramic fiber reinforcement is a short ceramic fiber and / or a continuous ceramic fiber preform, and the ceramic matrix contains Ti3SiC2 and SiC;

[0008] The ceramic fiber reinforced Ti3SiC2 / SiC composite material is formed by sintering a mixture of short ceramic fibers, a polycarbosilane precursor, a titanium source, and an additive under pressure.

[0009] Alternatively, the ceramic fiber reinforced Ti3SiC2 / SiC composite material is made of a continuous ceramic fiber preform and a slurry containing a polycarbosilane precursor, a titanium source, an additive, and a solvent through a precursor impregnation pyrolysis process (PIP).

[0010] Preferably, the fiber surface of the ceramic fiber reinforcement has an interface layer, and the interface layer includes one or more of carbon, silicon carbide, boron nitride and silicon nitride.

[0011] Preferably, the molecular main chain of the polycarbosilane precursor contains CH3SiHCH2 structural units and is solid at room temperature.

[0012] Preferably, the polycarbosilane precursor is polycarbosilane and / or polycarbosilane containing heterogeneous elements; the heterogeneous elements include one or more of aluminum, yttrium, nickel, hafnium, lithium, iron, cobalt, lanthanum, zirconium, titanium, beryllium, magnesium, calcium, vanadium and boron.

[0013] Further preferably, the polycarbosilane precursor includes one or more of iron-containing polycarbosilane (PFCS), zirconium-containing polycarbosilane (PZCS), boron-containing polycarbosilane (PBCS), yttrium-containing polycarbosilane (PYCS), and hafnium-containing polycarbosilane (PHfCS).

[0014] Preferably, the short ceramic fibers include one or more of silicon carbide fibers, silicon nitride fibers, alumina fibers, aluminum silicate fibers, quartz fibers, mullite fibers, calcium silicate fibers, zirconium oxide fibers, zirconium carbide fibers, hafnium carbide fibers, boron nitride fibers, and silicon-boron-carbon-nitrogen fibers.

[0015] Preferably, the continuous ceramic fiber preform is a ceramic fiber reinforcement formed by preforming continuous ceramic fibers into a specific shape using a shaping agent or a weaving method.

[0016] Further preferably, the continuous ceramic fiber includes one or more of silicon carbide fiber, silicon nitride fiber, alumina fiber, aluminum silicate fiber, quartz fiber, mullite fiber, calcium silicate fiber, zirconium oxide fiber, zirconium carbide fiber, hafnium carbide fiber, boron nitride fiber, and silicon-boron-carbon-nitrogen fiber.

[0017] Preferably, the thickness of the interface layer is 10 to 2000 nm.

[0018] Preferably, the titanium source includes one or more of Ti, TiH2, TiC, TiN, TiO2, and has an average particle size of 5 nm to 50 μm.

[0019] Preferably, the auxiliary agent includes one or more of Al powder, Mg powder, CaF2 powder, Zn powder, Cu powder and Ag powder, and the average particle size is 5nm to 50μm.

[0020] Preferably, the solvent includes one or more of toluene, xylene, tetrahydrofuran, n-hexane, chloroform and gasoline.

[0021] Preferably, the pressure sintering is carried out in an inert atmosphere, with an applied pressure of 0.1 to 200 MPa, a sintering temperature of 1000 to 1800° C., and a sintering time of 0.1 to 10 h.

[0022] Preferably, in the precursor impregnation pyrolysis process (PIP), the high temperature pyrolysis temperature is 1000-1800° C., the time is 0.1-10 h, and the heating rate is 0.1-20° C. / min.

[0023] Preferably, the precursor impregnation pyrolysis process (PIP) comprises:

[0024] (1) preparing a polycarbosilane precursor, a titanium source, an additive, and a solvent into a slurry;

[0025] (2) immersing the ceramic fiber reinforcement in the slurry in (1) under vacuum or pressure for 5 to 300 minutes to obtain an impregnated ceramic fiber reinforcement;

[0026] (3) drying the ceramic fiber reinforcement after impregnation in (2), placing it in a cracking furnace, and cracking it at high temperature in an inert atmosphere or a vacuum atmosphere to obtain a ceramic fiber reinforced Ti3SiC2 / SiC composite material preform;

[0027] (4) Repeat steps (1) to (3) until the weight gain rate of the ceramic fiber reinforced Ti3SiC2 / SiC composite material preform is less than 1%, thereby obtaining a ceramic fiber reinforced Ti3SiC2 / SiC composite material ceramic fiber reinforced Ti3SiC2 / SiC composite material finished product.

[0028] More preferably, the solid content of the slurry in (1) is 30 to 70%.

[0029] More preferably, in (1), the titanium source accounts for 1 to 80% of the mass of the polycarbosilane precursor, and the additive accounts for 0.5 to 20% of the mass of the titanium source.

[0030] More preferably, the immersion pressure in (2) is 1Pa to 5MPa; and the vacuum degree is less than 5Pa.

[0031] More preferably, the high temperature cracking temperature in (3) is 1000-1800°C, the time is 0.1-10h, and the heating rate is 0.1-20°C / min.

[0032] Preferably, the ceramic fiber reinforced Ti3SiC2 / SiC composite material has a bending strength of ≥200Mpa, an electrical conductivity of ≥2000S / m, and a minimum reflection loss RL of ≤-20dB.

[0033] Further preferably, the ceramic fiber reinforced Ti3SiC2 / SiC composite material has a bending strength of ≥250Mpa, an electrical conductivity of ≥3000S / m, and a minimum reflection loss RL of ≤-25dB.

[0034] A method for preparing a ceramic fiber reinforced Ti3SiC2 / SiC composite material, comprising:

[0035] The mixture of short ceramic fibers, polycarbosilane precursor, titanium source and additives is sintered under pressure.

[0036] Alternatively, the ceramic fiber reinforced Ti3SiC2 / SiC composite material is made of a continuous ceramic fiber preform and a slurry containing a polycarbosilane precursor, a titanium source, an additive, and a solvent through a precursor impregnation pyrolysis process (PIP).

[0037] Preferably, the preparation method of the ceramic fiber reinforced Ti3SiC2 / SiC composite material comprises:

[0038] The short ceramic fiber, a mixture of a polycarbosilane precursor, a titanium source and an additive are sintered under pressure; the pressure sintering is carried out in an inert atmosphere, with an applied pressure of 0.1 to 200 MPa, a sintering temperature of 1000 to 1800° C. and a sintering time of 0.1 to 10 hours.

[0039] More preferably, the short ceramic fiber has an interface layer on its surface, and the interface layer includes one or more of carbon, silicon carbide, boron nitride, and silicon nitride.

[0040] Preferably, the preparation method of the ceramic fiber reinforced Ti3SiC2 / SiC composite material comprises:

[0041] (1) preparing a polycarbosilane precursor, a titanium source, an additive, and a solvent into a slurry;

[0042] (2) immersing the continuous ceramic fiber preform in the slurry in (1) under vacuum and / or pressure for 5 to 300 minutes;

[0043] (3) drying the continuous ceramic fiber preform impregnated in (2), placing it in a cracking furnace, and cracking it at high temperature in an inert atmosphere or a vacuum atmosphere to obtain a ceramic fiber reinforced Ti3SiC2 / SiC composite material preform;

[0044] (4) Repeat steps (1) to (3) until the weight gain rate of the ceramic fiber reinforced Ti3SiC2 / SiC composite material preform is less than 1%, thereby obtaining a ceramic fiber reinforced Ti3SiC2 / SiC composite material ceramic fiber reinforced Ti3SiC2 / SiC composite material finished product.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The ceramic fiber reinforced Ti3SiC2 / SiC composite material of the present invention consists of a ceramic fiber reinforcement and a ceramic matrix; the ceramic fiber reinforcement is a short ceramic fiber and / or a continuous ceramic fiber preform, and the ceramic matrix contains Ti3SiC2 and SiC.

[0047] 2. The ceramic matrix in the ceramic fiber reinforced Ti3SiC2 / SiC composite material of the present invention uses polycarbosilane, titanium source and additives as raw materials of the composite matrix, and generates Ti3SiC2 and SiC in situ after pressure sintering or impregnation cracking. The structural components are relatively uniform and the components are tightly combined.

[0048] 3. The present invention introduces the Ti3SiC2 structure into the SiC composite material in situ, which is beneficial to improving the electrical conductivity, electromagnetic absorption, anti-oxidation and other properties of the composite material.

[0049] 4. The preparation method of the ceramic fiber reinforced Ti3SiC2 / SiC composite material of the present invention is simple and controllable, and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The SiC in Example 1 of the present invention f X-ray diffraction (XRD) pattern of / Ti3SiC2 / SiC composite material 1.

[0051] Figure 2 The SiC in Example 1 of the present invention f Scanning electron microscope (SEM) image of / Ti3SiC2 / SiC composite material 1. DETAILED DESCRIPTION

[0052] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not used to specifically limit the present invention.

[0053] Unless otherwise specified, the materials used in the present invention are commercially available raw materials commonly used in the art, and the methods used are conventional technical means in the art.

[0054] Example 1

[0055] The continuous SiC f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0056] (1) A pyrolytic carbon interface layer was prepared on the surface of SiC fiber cloth (commercially available) by chemical vapor deposition, and the thickness of the pyrolytic carbon layer was 200 nm;

[0057] (2) Take 50 g of polycarbosilane (PCS), add 50 g of xylene, 50 g of Ti powder, and 5 g of Al powder, and stir to prepare an impregnation slurry;

[0058] (3) Then, the SiC fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 2 MPa to obtain a PCS-TiO1 sample;

[0059] (4) The PCS-Ti01 sample was placed in a drying oven and dried at 60°C for 5 h to remove the solvent; then the sample was placed in a cracking furnace and heated to 1200°C at 2°C / min under the protection of an argon atmosphere, and kept at this temperature for 1 h to obtain a PCS-Ti01 preform;

[0060] (5) Repeat steps (3) to (4) until the weight gain of the PCS-TiO1 preform is less than 1%, and obtain SiC f / Ti3SiC2 / SiC composite material1.

[0061] Figure 1 In this embodiment, continuous SiC f XRD pattern of / Ti3SiC2 / SiC composite material 1; Figure 2 SiC f / Ti3SiC2 / SiC composite material 1 SEM image. It can be seen that

[0062] After three-point bending strength test, SiC f The bending strength of the / Ti3SiC2 / SiC composite material 1 is 310Mpa; the electrical performance test shows that SiC f The conductivity of the / Ti3SiC2 / SiC composite material 1 is 6000S / m; the wave absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -40dB.

[0063] Example 2

[0064] The continuous SiC fThe preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0065] (1) The thickness of the pyrolytic carbon interface layer was prepared by chemical vapor deposition on the surface of SiC fiber cloth (commercially available), and the thickness of the pyrolytic carbon layer was 230 nm;

[0066] (2) Take 50 g of aluminum-containing polycarbosilane (PACS), add 50 g of xylene, 40 g of TiH2 powder, and 5 g of Mg powder, and prepare an impregnation slurry by ultrasonic dispersion;

[0067] (3) Then, the silicon carbide fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 1 MPa to obtain a PACS-TiO1 sample;

[0068] (4) placing the PACS-01 sample in a drying oven, heating it to 70°C and keeping it for 5 hours to remove the solvent; placing the sample after the solvent is removed in a cracking furnace, heating it to 1600°C at 2°C / min under the protection of an argon atmosphere, and keeping it at this temperature for 2 hours to obtain a PACS-Ti01 preform;

[0069] (5) Repeat steps (3) to (4) until the weight gain of the composite material is less than 1%, and obtain SiC f / Ti3SiC2 / SiC composite material2.

[0070] After three-point bending strength test, SiC f The bending strength of the / Ti3SiC2 / SiC composite material 2 is 400Mpa; the electrical performance test shows that SiC f The conductivity of the / Ti3SiC2 / SiC composite material 2 is 10000S / m; the absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -45dB.

[0071] Example 3

[0072] The SiC of this embodiment f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0073] (1) 20 g of SiC short fiber, 50 g of polycarbosilane (PCS), 40 g of TiH2 powder, and 3 g of CaF2 powder were ball-milled to form a uniform mixture;

[0074] (3) Then the mixture is placed in a mold for hot pressing and sintering. The hot pressing and sintering conditions are: inert atmosphere, applied pressure of 100 MPa, sintering temperature of 1400°C, and sintering time of 1 hour. SiC is obtained. f / Ti3SiC2 / SiC composite material3.

[0075] After three-point bending strength test, SiCf The bending strength of the Ti3SiC2 / SiC composite material 3 is 450Mpa; the electrical performance test shows that the SiC f The conductivity of the / Ti3SiC2 / SiC composite material 3 is 7000S / m; the absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -45dB.

[0076] Example 4

[0077] The continuous Si3N 4f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0078] (1) The surface of silicon nitride Si3N4 fiber cloth (commercially available) is subjected to chemical vapor deposition to prepare a BN interface layer with a thickness of 200 nm to 300 nm;

[0079] (2) Take 50 g of iron-containing polycarbosilane (PFCS), add 50 g of xylene, 40 g of TiN powder, and 5 g of Zn powder to prepare an impregnation slurry through ultrasonic dispersion;

[0080] (3) Then, the silicon nitride fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 2 MPa to obtain a PFCS-TiO1 sample;

[0081] (4) placing the PFCS-Ti01 sample in a drying oven, heating it to 60°C and keeping it for 5 hours to remove the solvent; placing the sample after the solvent is removed in a cracking furnace, heating it to 1200°C at 2°C / min under the protection of an argon atmosphere, and keeping it at this temperature for 1 hour to obtain a PFCS-Ti01 preform;

[0082] (5) Repeat steps (3) to (4) until the weight gain of the composite material is less than 1%, and obtain Si3N 4f / Ti3SiC2 / SiC composite material1.

[0083] After three-point bending strength test, Si3N 4f The bending strength of the composite material 1 is 400Mpa; the electrical performance test shows that Si3N 4f The electrical conductivity of the Ti3SiC2 / SiC composite material 1 is 4000S / m; the wave absorbing performance is tested by a vector network analyzer, and the minimum reflection loss RL is -30dB.

[0084] Example 5

[0085] The continuous Al2O 3f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0086] (1) a SiC interface layer is prepared on the surface of an alumina Al2O3 fiber cloth (commercially available) by chemical vapor deposition, wherein the thickness of the SiC interface layer is 200 to 300 nm;

[0087] (2) Take 50 g of zirconium-containing polycarbosilane (PZCS), add 50 g of xylene, 40 g of TiO2 powder, and 3 g of Al powder, and prepare an impregnation slurry by ultrasonic dispersion;

[0088] (3) Then, the Al2O3 fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 1.5 MPa to obtain a PZCS-TiO1 sample;

[0089] (4) placing the PZCS-Ti01 sample in a drying oven, heating it to 80°C and keeping it for 3 hours to remove the solvent; placing the sample after the solvent is removed in a cracking furnace, heating it to 1600°C at 2°C / min under the protection of an argon atmosphere, and keeping it at this temperature for 1 hour to obtain a PZCS-Ti01 preform;

[0090] (5) Repeat steps (3) to (4) until the weight gain of the composite material is less than 1%, and obtain Al2O 3f / Ti3SiC2 / SiC composite material1.

[0091] The three-point bending strength test shows that Al2O 3f The bending strength of the / Ti3SiC2 / SiC composite material 1 is 350Mpa; the electrical performance test shows that the Al2O 3f The conductivity of the / Ti3SiC2 / SiC composite material 1 is 3050S / m; the wave absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -45dB.

[0092] Example 6

[0093] The continuous SiO 2f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0094] (1) A SiC interfacial layer with a thickness of 100 to 150 nm was prepared on the surface of a continuous SiO2 fiber cloth (commercially available) by chemical vapor deposition;

[0095] (2) Take 50 g of boron-containing polycarbosilane (PBCS), add 55 g of chloroform, 30 g of Ti powder, 10 g of TiC powder, 10 g of TiH2 powder, and 5 g of Al powder, and prepare an impregnation slurry by ultrasonic dispersion;

[0096] (3) Then, the SiO2 fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 1 MPa to obtain a PBCS-TiO1 sample;

[0097] (4) placing the PBCS-Ti01 sample in a drying oven, heating it to 80°C and keeping it for 3 hours to remove the solvent; placing the sample after the solvent is removed in a cracking furnace, heating it to 1100°C at 2°C / min under the protection of an argon atmosphere, and keeping it at this temperature for 1 hour to obtain a PBCS-Ti01 preform;

[0098] (5) Repeat steps (3) to (4) until the weight gain of the composite material is less than 1%, and obtain SiO 2f / Ti3SiC2 / SiC composite material1.

[0099] After three-point bending strength test, SiO 2f The bending strength of the / Ti3SiC2 / SiC composite material 1 is 250Mpa; the electrical performance test shows that the SiO 2f The conductivity of the / Ti3SiC2 / SiC composite material 1 is 2500S / m; the wave absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -25dB.

[0100] Example 7

[0101] The continuous SiBCN of this embodiment f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0102] (1) Carbon and SiC interface layers were prepared on the surface of SiBCN fiber cloth (commercially available) by chemical vapor deposition, with the carbon layer thickness being 200 nm and the SiC layer thickness being 100 nm;

[0103] (2) 50 g of yttrium-containing polycarbosilane (PYCS) was added with 55 g of chloroform, 45 g of Ti powder, and 4 g of Mg powder to prepare an impregnation slurry by ultrasonic dispersion;

[0104] (3) Then, the SiBCN fiber cloth prepared in (1) is placed in the impregnation slurry and impregnated under a gas pressure of 2 MPa to obtain a PYCS-TiO1 sample;

[0105] (4) placing the PYCS-Ti01 sample in a drying oven, heating it to 50°C and keeping it for 5 hours to remove the solvent; placing the sample after the solvent is removed in a cracking furnace, heating it to 1600°C at 2°C / min under the protection of an argon atmosphere, and keeping it at this temperature for 1 hour to obtain a PYCS-Ti01 preform;

[0106] (5) Repeat steps (3) to (4) until the weight gain of the composite material is less than 1% to obtain SiBCN f / Ti3SiC2 / SiC composite material1.

[0107] After three-point bending strength test, SiBCN fThe bending strength of the / Ti3SiC2 / SiC composite material 1 is 400Mpa; the electrical performance test shows that the SiBCN f The conductivity of the / Ti3SiC2 / SiC composite material 1 is 3500S / m; the absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -43dB.

[0108] Example 8

[0109] The ZrC in this embodiment f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0110] (1) 20 g of zirconium carbide ZrC short fibers, 50 g of hafnium-containing polycarbosilane (PHfCS), 40 g of TiH2 powder, and 3 g of Al powder were ball-milled to form a uniform mixture;

[0111] (3) Then the mixture was placed in a mold for spark plasma sintering. The sintering conditions were: inert atmosphere, applied pressure of 80 MPa, sintering temperature of 1600°C, and sintering time of 15 h to obtain ZrC f / Ti3SiC2 / SiC composite material1.

[0112] After three-point bending strength test, ZrC f The bending strength of the / Ti3SiC2 / SiC composite material 1 is 350Mpa; the electrical performance test shows that the ZrC f The conductivity of the / Ti3SiC2 / SiC composite material 1 is 5000S / m; the absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -35dB.

[0113] Comparative Example 1

[0114] Compared with Example 1, the difference is that the impregnation slurry of this comparative example only contains polycarbosilane precursor and solvent.

[0115] The continuous SiC f The preparation method of the / SiC composite material is as follows:

[0116] (1) A pyrolytic carbon interface layer was prepared on the surface of SiC fiber cloth (commercially available) by chemical vapor deposition, and the thickness of the pyrolytic carbon layer was 200 nm;

[0117] (2) Take 50 g of polycarbosilane precursor PCS, add 50 g of xylene and stir to prepare an impregnation slurry;

[0118] (3) Then, the SiC fiber cloth prepared in (1) was placed in the impregnation slurry and impregnated under a gas pressure of 2 MPa to obtain a PCS-01 sample;

[0119] (4) The PCS-01 sample was placed in a drying oven and dried at 60°C for 5 h to remove the solvent; then the sample was placed in a cracking furnace and heated to 1200°C at a rate of 2°C / min under the protection of an argon atmosphere, and kept at this temperature for 1 h to obtain a PCS-01 preform;

[0120] (5) Repeat steps (3) to (4) until the weight gain of the PCS-01 preform is less than 1%, and obtain SiC f / SiC composite material1.

[0121] After three-point bending strength test, SiC f The bending strength of the SiC composite material 1 is 380Mpa; the electrical performance test shows that the SiC f The conductivity of the / SiC composite material 1 is 50S / m; the wave absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -5dB.

[0122] Comparative Example 2

[0123] Compared with Example 1, the difference is that Ti3SiC2 ceramic powder is directly added to the impregnation slurry in this comparative example.

[0124] The continuous SiC f The preparation method of the / Ti3SiC2 / SiC composite material is as follows:

[0125] (1) A pyrolytic carbon interface layer was prepared on the surface of SiC fiber cloth (commercially available) by chemical vapor deposition, and the thickness of the pyrolytic carbon layer was 200 nm;

[0126] (2) adding Ti3SiC2 ceramic powder to a ball mill for ball milling pretreatment to obtain pretreated ceramic powder with an average particle size of 0.1 μm; taking 50 g of polycarbosilane precursor PCS, adding 50 g of xylene, and then adding the pretreated ceramic powder, and preparing an impregnation slurry by stirring;

[0127] (3) Then, the SiC fiber cloth prepared in (1) was placed in the impregnation slurry and impregnated under a gas pressure of 2 MPa to obtain a PCS-02 sample;

[0128] (4) The PCS-02 sample was placed in a drying oven and dried at 60°C for 5 h to remove the solvent; then the sample was placed in a cracking furnace and heated to 1200°C at 2°C / min under the protection of an argon atmosphere, and kept at this temperature for 1 h to obtain a PCS-02 preform;

[0129] (5) Repeat steps (3) to (4) until the weight gain of the PCS-02 preform is less than 1%, and obtain SiC f / Ti3SiC2 / SiC composite material4.

[0130] After three-point bending strength test, SiC f The bending strength of the / Ti3SiC2 / SiC composite material 4 is 200Mpa; the electrical performance test shows that SiC f The electrical conductivity of the / Ti3SiC2 / SiC composite material 2 is 4000S / m; the wave absorption performance is tested by a vector network analyzer, and the minimum reflection loss RL is -25dB.

[0131] In summary, the ceramic fiber reinforced Ti3SiC2 / SiC composite material of the present invention consists of a ceramic fiber reinforcement and a ceramic matrix; the ceramic fiber reinforcement is a short ceramic fiber and / or a continuous ceramic fiber preform, and the ceramic matrix includes Ti3SiC2 and SiC; the Ti3SiC2 structure is introduced in situ into the SiC composite material, which is beneficial to improving the electrical conductivity, electromagnetic absorption, anti-oxidation and other properties of the composite material.

[0132] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A ceramic fiber reinforced Ti3SiC2 / SiC composite material, characterized in that: It consists of a ceramic fiber reinforcement and a ceramic matrix; the ceramic fiber reinforcement is a short ceramic fiber and / or a continuous ceramic fiber preform, and the ceramic matrix contains Ti3SiC2 and SiC; The ceramic fiber reinforced Ti3SiC2 / SiC composite material is formed by sintering a mixture of short ceramic fibers, a polycarbosilane precursor, a titanium source, and an additive under pressure. Alternatively, the ceramic fiber reinforced Ti3SiC2 / SiC composite material is made of a continuous ceramic fiber preform and a slurry containing a polycarbosilane precursor, a titanium source, an additive, and a solvent through a precursor impregnation and cracking process.

2. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The surface of the ceramic fiber reinforcement is provided with an interface layer, and the interface layer includes one or more of carbon, silicon carbide, boron nitride and silicon nitride.

3. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The molecular backbone of the polycarbosilane precursor contains CH3SiHCH2 structural units and is solid at room temperature; the polycarbosilane precursor is polycarbosilane and / or polycarbosilane containing heterogeneous elements; the heterogeneous elements include one or more of aluminum, yttrium, nickel, hafnium, lithium, iron, cobalt, lanthanum, zirconium, titanium, beryllium, magnesium, calcium, vanadium, and boron.

4. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The short ceramic fibers include one or more of silicon carbide fibers, silicon nitride fibers, alumina fibers, aluminum silicate fibers, quartz fibers, mullite fibers, calcium silicate fibers, zirconium oxide fibers, zirconium carbide fibers, hafnium carbide fibers, boron nitride fibers, and silicon-boron-carbon-nitrogen fibers.

5. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The continuous ceramic fiber preform is a ceramic fiber reinforcement formed by preforming continuous ceramic fibers using a shaping agent or a weaving method; the continuous ceramic fibers include one or more of silicon carbide fibers, silicon nitride fibers, alumina fibers, aluminum silicate fibers, quartz fibers, mullite fibers, calcium silicate fibers, zirconium oxide fibers, zirconium carbide fibers, hafnium carbide fibers, boron nitride fibers, and silicon-boron-carbon-nitrogen fibers.

6. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The titanium source includes one or more of Ti, TiH2, TiC, TiN, and TiO2, and has an average particle size of 5nm to 50μm.

7. The ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 1, characterized in that: The auxiliary agent includes one or more of Al powder, Mg powder, CaF2 powder, Zn powder, Cu powder and Ag powder, and the average particle size is 5nm-50μm.

8. A method for preparing the ceramic fiber reinforced Ti3SiC2 / SiC composite material as claimed in claim 1, characterized in that: The preparation method comprises: The mixture of short ceramic fibers, polycarbosilane precursor, titanium source and additives is sintered under pressure. Alternatively, the ceramic fiber reinforced Ti3SiC2 / SiC composite material is made of a continuous ceramic fiber preform and a slurry containing a polycarbosilane precursor, a titanium source, an additive, and a solvent through a precursor impregnation and cracking process.

9. The method for preparing the ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 8, characterized in that: The preparation method comprises: short ceramic fibers and a mixture of a polycarbosilane precursor, a titanium source and an auxiliary agent are sintered under pressure; the pressure sintering is performed under an inert atmosphere, with an applied pressure of 0.1 to 200 MPa, a sintering temperature of 1000 to 1800° C. and a sintering time of 0.1 to 10 hours.

10. The method for preparing the ceramic fiber reinforced Ti3SiC2 / SiC composite material according to claim 8, characterized in that: The preparation method comprises: (1) preparing a polycarbosilane precursor, a titanium source, an additive, and a solvent into a slurry; (2) immersing the continuous ceramic fiber preform in the slurry in (1) under vacuum and / or pressure for 5 to 300 minutes; (3) drying the continuous ceramic fiber preform impregnated in (2), placing it in a cracking furnace, and cracking it at high temperature in an inert atmosphere or a vacuum atmosphere to obtain a ceramic fiber reinforced Ti3SiC2 / SiC composite material preform; (4) Repeat steps (1) to (3) until the weight gain rate of the ceramic fiber reinforced Ti3SiC2 / SiC composite material preform is less than 1%, thereby obtaining a ceramic fiber reinforced Ti3SiC2 / SiC composite material ceramic fiber reinforced Ti3SiC2 / SiC composite material finished product.

Citation Information

Cited By

  • Ceramic composite cutter with high hardness and wear resistance and preparation method thereof

    CN122235555A

  • MAX-phase brazed joint for homogeneous welding of ceramic matrix composite and preparation method of MAX-phase brazed joint

    CN122502203A